Drivers of the lifecycle: the example of the German insurance industry - Michael Menhart; Carsten Rennhak (Hochschule Reutlingen, School of International Business (SIB), 2006)
Lifecycles have been accepted widely as a matter of fact in business. Existing literature focuses on their theoretical implications for product managers and corporate strategists. There are major shortcomings of the research in that field concerning the populations covered (if at all, mostly hardware) and the theoreticcal as well as empirical analysis of the drivers of the lifecycles in the various industries. Based on the research of Menhart et al. (2003), we chose a population of service organizations to analyze the drivers of the lifecycle. Biological lifecycles describe the development processes of an individual from birth to death. Economic life cycle concepts assume, that in analogy to biological organisms, economic systems also experience typical phases of development in their evolution. In the economic literature, life cycle concepts were used to explain the development patterns of single products, organizations, technologies and whole industries. In the standard model of the life cycle concept, specific characteristics of the unit of analysis such as sales volume, turnover or number of competitors first increase to a maximum, then decrease significantly and finally reach a level of stability, or they are discontinued completely. We have developed a concept for an insurance specific industry life cycle with a non-typical maturation and degeneration phase, and discuss to what extent the concept of Maslow's pyramid of needs can have explanatory power regarding the pattern of density dynamics. – – Lebenszyklen sind in der wirtschaftswissenschaftlichen Forschung inzwischen ein etabliertes Konzept, wobei der Großteil der vorhandenen Literatur auf Normstrategien in Produktmanagement oder auf Unternehmensebene abstellt. Industriepopulation wurden bislang dagegen ebenso wenig untersucht (und wenn, dann ausschließlich im Sachgüterbereich) wie die theoretische oder praktische Triebkräfte für Veränderungen von Industriepopulationen. Basierend auf den Forschungsergebnissen von Menhart et al. (2003) untersuchen wir die Treiber des Lebenszyklus für eine Population von Dienstleistungsunternehmen. Biologische Lebenszyklen beschreiben das Leben eines Individuums von der Geburt bis zum Tode. Ökonomische Lebenszyklen liegt die Annahme zugrunde, dass - analog zu den biologischen Organismen - auch ökonomische Systeme typische Evolutionsphasen in ihrer Entwicklung durchlaufen. In der Literatur werden Lebenszykluskonzepte zur Erklärung der Entwicklungsverläufe einzelner Produkte, von Organisationen, Technologien und ganzen Industrien genutzt. Im Standardmodell des Lebenszyklus wachsen spezifische Charakteristika des Untersuchungsgegenstands wie z.B. Absatz, Umsatz oder Anzahl der Mitbewerber zunächst auf ein Maximum an, um dann signifikant zurück zu gehen und sich schließlich auf ein stabiles Maß einzupendeln. In extremen Fällen endet der Lebenszyklus auch abrupt. Wir haben ein spezifisches Konzept für Industrielebenszyklen in der Versicherungsbranche entwickelt, das einen untypischen Verlauf in der Reife- und Degenerationsphase zeigt. Weiter diskutieren wir, inwieweit die Maslowsche Bedürfnispyramide ein möglicher Erklärungsansatz für Veränderungen in der Populationsdichte ist.
urn:nbn:de:bsz:21-opus-30985
Keywords: 650